Domain adaptation and representation transfer and medical image learning with less labels and imperfect data : first MICCAI Workshop, DART 2019, and first International Workshop, MIL3ID 2019, Shenzhen, Held in Conjunction with MICCAI 2019, Shenzhen, China, October 13 and 17, 2019, Proceedings /: first MICCAI Workshop, DART 2019, and first International Workshop, MIL3ID 2019, Shenzhen, Held in Conjunction with MICCAI 2019, Shenzhen, China, October 13 and 17, 2019, Proceedings. (2019) - Unknown
No abstract available